Melatonin and omega-3 neuroprotection in prenatal rat spinal cord exposed to 900 MHz electromagnetic field - Ömür Gülsüm Deniz; Gamze Altun; Süleyman Kaplan (Biomolecules & Biomedicine)
The electromagnetic field (EMF) emitted by electronic devices induces pathological changes in tissues, adversely affecting embryonic and pubertal development. This study investigates the effects of melatonin (Mel) and omega-3 fatty acids (ω3) on the spinal cord in rats exposed to EMF, employing stereological methods alongside light and electron microscopic evaluations. Pregnant Wistar albino rats were divided into seven groups: Control (CONT), sham-exposed (SHAM), EMF alone, EMF-Mel, EMF-ω3, Mel only, and ω3 only. The EMF, EMF-Mel, and EMF-ω3 groups were exposed to a 900 MHz EMF for two hours daily during the prenatal period (21 days). Mel and ω3 were administered via intragastric gavage prior to EMF exposure. Upon completion of the experiment (on the 35th day post-birth), spinal cord tissues of all male offspring were dissected and subjected to light and ultrastructural examinations. Stereological analyses calculated grey matter (GM) to total volume ratios, white matter (WM) to total volume ratios, GM to WM volume ratios, total spinal cord volume, and motor neuron counts. No significant differences were observed among the groups regarding GM/WM volume ratios, GM/total volume ratios, WM/total volume ratios, and total spinal cord volume (p > 0.05). However, a significant reduction in motor neuron numbers was noted in the EMF-ω3 group compared to the CONT group (p < 0.01). Light and ultrastructural examinations revealed marked motor neuron degeneration and axonal disruption in the EMF group, which were mitigated in the Mel and ω3-treated groups. These findings indicate that prenatal exposure to 900 MHz EMF exerts detrimental effects on spinal cord tissue and underscore the necessity for further studies exploring varying doses and durations to elucidate the potential effects of ω3 and Mel.